Collection Module Data To Support a Pedagogical Agent Affective - Rosa, Marcus; Konzen, Andrea Aparecida (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper describes the development of a module to collect quantitative data in order to assist a computacional pedagogical and affective agent called 'MagaVitta'. This agent is part of the virtual game simulation of cities called 'Città'. The data collected by this module will assist the affective pedagogical agent to understand the current state of the simulation, allowing to infer emotions and display messages that will assist the student in the construction of the city in order to learn how to maintain the ecological balance of the city.